Disasters in the Republic of Turkey According to the International Disaster Database - Hande Bahadır; Reyhan Uçku (Doğal Afetler ve Çevre Dergisi)
The Emergency Events Database is a free database containing 115 years’ worth of data for natural and technological disasters. In this study, it is aimed to investigate the distribution of disasters and death figures from the foundation of the Republic of Turkey until the end of 2016. Disasters, which occurred in Turkey between 1923 and 2016 were included in this descriptive study. Data were analyzed using SPSS version 15.0 software and descriptive results were presented as frequency. 313 disasters were found in the database between the years 1923-2016 within the Turkish Republic borders. 51.1% of them are natural disasters. The highest number of disasters occurred in 2004 while the highest death happened in 1939. Earthquakes constitute 24.3% of all disasters. The earthquake, which is considered as an unavoidable, is a disaster which can be largely prevented by personal, environmental, structural preventions. In order to avoid deaths, living in earthquake-resistance houses should be encouraged, personal and environmental risks should be assessed and protection trainings should be increased.